Acquired Haemophilia due to Factor-VIII Inhibitors Secondary to Bladder Malignancy: A Case Report - Shumail, Shabana; Junaid, Dr. Ayesha; Rashid, Kamran (International Journal of Pathology, 2018)
Acquired hemophilia A (AHA) is a severe bleeding diathesis caused by the appearance of autoantibodies againstcoagulation factor VIII (FVIII). Clinical features of inherited and acquired hemophilia are spontaneous as well asposttraumatic deep muscle-joint and mucosal bleeding. 50% cases of AHA are associated with autoimmune diseases,malignancies, medications and the postpartum period, but in the rest of the patients development of FVIII autoantibodies isidiopathic. Unexplained prolonged activated partial thromboplastin time (APTT) without previous history of bleeding shouldwarrant work up for AHA. AHA secondary to bladder malignancy is rare with only three cases reported till to-date. Wereport a case of an elderly male who developed acquired hemophilia secondary to bladder malignancy and presented with arare clinical presentation of hemarthrosis.